Radio observations of supernova remnant G1.9+0.3 - Luken, KJ; Filipovic, MD; Maxted, NI; Kothes, R; Norris, RP; Allison, JR; Blackwell, R; Braiding, C; Brose, R; Burton, M; De Horta, AY; Galvin, TJ; et al. (Oxford University Press, 2019)
We present 1–10 GHz radio continuum flux density, spectral index, polarization, and rotation measure (RM) images of the youngest known Galactic supernova remnant (SNR) G1.9+0.3, using observations from the Australia Telescope Compact Array. We have conducted an expansion study spanning eight epochs between 1984 and 2017, yielding results consistent with previous expansion studies of G1.9+0.3. We find a mean radio continuum expansion rate of (0.78 ± 0.09) per cent yr−1 (or ∼8900 km s−1 at an assumed distance of 8.5 kpc), although the expansion rate varies across the SNR perimetre. In the case of the most recent epoch between 2016 and 2017, we observe faster-than-expected expansion of the northern region. We find a global spectral index for G1.9+0.3 of −0.81 ± 0.02 (76 MHz–10 GHz). Towards the northern region, however, the radio spectrum is observed to steepen significantly (∼−1). Towards the two so-called (east and west) ‘ears’ of G1.9+0.3, we find very different RM values of 400–600 and 100–200 rad m2, respectively. The fractional polarization of the radio continuum emission reaches (19 ± 2) per cent, consistent with other, slightly older, SNRs such as Cas A.